The Unified Theory Acceptance and Use of Technology in the Industrial Internet of Things Era: A Conceptual Framework - Ridhwan, Nugroho; Purwanto, Edi (KnE Social Sciences, 2020)
The purpose of this article is to build a conceptual framework based on literature review that will be tested in future research related to Digital Business. The results of the literature review allow for the construction of hypotheses into a conceptual framework. Furthermore, the study assesses the influence of performance expectations, efforts expectations and social influence on behavioral intention and usage behavior by modifying Hofstede’s cultural dimensions. The conceptual framework will be tested among Industrial Internet of Things (IIoT) users for future research in Indonesia. Keywords: performance expectancy, effort expectancy, social influence, behavioral intention, use behavior, UTAUT, Hofstede’s cultural dimensions, Industrial IoT